Hermite-Hadamard, Jensen, and Fractional Integral Inequalities for Generalized P-Convex Stochastic Processes - Fangfang Ma; Waqas Nazeer; Mamoona Ghafoor (Journal of Mathematics)
The stochastic process is one of the important branches of probability theory which deals with probabilistic models that evolve over time. It starts with probability postulates and includes a captivating arrangement of conclusions from those postulates. In probability theory, a convex function applied on the expected value of a random variable is always bounded above by the expected value of the convex function of that random variable. The purpose of this note is to introduce the class of generalized p-convex stochastic processes. Some well-known results of generalized p-convex functions such as Hermite-Hadamard, Jensen, and fractional integral inequalities are extended for generalized p-stochastic convexity.